Effects of tofacitinib on nucleic acid metabolism in human articular chondrocytes. Issue 4 (July 2015) - Koizumi, Hideki; Arito, Mitsumi; Endo, Wataru; Kurokawa, Manae S.; Okamoto, Kazuki; Omoteyama, Kazuki; Suematsu, Naoya; Beppu, Moroe; Kato, Tomohiro
Abstract: Objective . In our previous screening of chondrocyte protein profiles, the amount of adenosine monophosphate deaminase (AMPD) 2 was found to be decreased by tofacitinib. Extending the study, here we confirmed the decrease of AMPD2 by tofacitinib and further investigated effects of tofacitinib on purine nucleotide metabolism. Methods . Human articular chondrocytes and a chondrosarcoma cell line: OUMS-27 were stimulated with tofacitinib. Then the levels of AMPD2 and its related enzymes were investigated by Western blot. The levels of AMP and adenosine were assessed by mass spectrometry. Results . We confirmed the significant decrease of AMPD2 by tofacitinib in chondrocytes ( p = 0.025). The levels of adenosine kinase and 5'-nucleotidase were decreased in chondrocytes, although they did not meet statistical significance ( p = 0.067 and p = 0.074, respectively). The results from OUMS-27 were similar to those from the chondrocytes. The cellular adenosine levels were significantly decreased by tofacitinib in OUMS-27 ( p = 0.014). The cellular AMP levels were increased, although they did not meet statistical significance in OUMS-27 ( p = 0.066). Conclusion . Our data indicate that tofacitinib increases the cellular levels of adenosine, which is known to have anti-inflammatory activity, through the downregulation of AMPD2. This would be a novel functional aspect of tofacitinib.